EKRANISASI NOVEL SABTU BERSAMA BAPAK KARYA ADHITYA MULYA KE FILM SABTU BERSAMA BAPAK KARYA SUTRADARA MONTY TIWA - Parmi, Ami Wisda; Nasution, Bakhtarudin; Nst., Muhammad Ismail (Universitas Negeri Padang, 2017)
This study aimed to: (a) describe the episodes of the novel Sabtu Bersama Bapak by Adhitya Mulya, (b) describe the episodes of the film Sabtu Bersama BapakÂ directed by Monty Tiwa, (c) describe the comparison of episodes in the novel Sabtu Bersama Bapak by Adhitya Mulya with Film Sabtu Bersama BapakÂ by Monty Tiwa. This research is a qualitative research with descriptive method. This research data is the episode of the novel Sabtu Bersama Bapak by Mulya and film Sabtu Bersama Bapak by Monty TiwaThe technique of data validation is done by detailed description. Analyzing technique is done by the theory of ekranisasi. The results obtained from this research are the 192 episodes of the novel Sabtu Bersama Bapak by Adhitya Mulya, 127 episodes of the movie's Sabtu Bersama Bapak director Monty Tiwa and 83 episodes of the same story contained in novel Sabtu Bersama Bapak by Adhitya Mulya and film Sabtu Bersama Bapak by Monty Tiwa who experienced changes in variations of events, characters and background. It happens because of the creation of the director while adapting the novel to the movie.Keywords : novel, movie, ekranisasi